Jewish thought in dialogue essays on thinkers, theologies, and moral theories - Shatz, David (Judaism and Jewish life., 2009)
"The essays in this volume present interpretations of themes in major Jewish texts and thinkers, as well as treatments of significant issues in Jewish theology and ethics. It offers philosophical readings of biblical narratives, analyses of topics in the thought of Maimonides, Rabbi Abraham Isaac Kook and Rabbi Joseph B. Soloveitchik, and critical and constructive examinations of divine providence, religious anthropology, free will, 9/11, evil, Halakhah and morality, altruism, autonomy in Jewish medical ethics, and the epistemology of religious belief. The author frequently brings Jewish philosophy and law into dialogue with contemporary Anglo-American philosophy. The book serves scholars and students of Jewish philosophy and law, and is suitable for inclusion in syllabi of undergraduate and graduate courses''--Provided by the publisher.